'Global sociology' in different disciplinary practices: Current conditions, problems and perspectives. (January 2016) - Sorokin, Pavel
This article discusses perspectives for the formation of a truly 'global sociology', implying active, open, mutually beneficial and equal interaction between sociologists from different locations, countries and cultures, in their joint efforts to comprehend, explain and improve the social world. The study is based on the conceptual scheme proposed by Burawoy, highlighting four different disciplinary practices: 'professional sociology', 'policy sociology', 'critical sociology' and 'public sociology'. The formation of a 'global sociology' demands harmonious development and mutual enrichment between all the four 'sociologies', however, each of them has its own path in the global arena. The literature analysis demonstrates serious limitations in the global progression of 'professional sociology', while 'policy sociology' and 'critical sociology' also experience major difficulties. 'Public sociology', largely inspired by Burawoy, seems to be especially promising globally due to its key advantages: orientation towards non-academic audiences and a focus on the most acute social problems. However, currently this disciplinary practice has several fundamental constraints: marginality, radicalism, ideological bias and inherent conflict-orientation towards other 'sociologies'. Drawing on John Meyer's theory of 'Scientized Environment Supporting Actorhood', the article proposes the project of the new 'Global Solidarity Sociology', which utilizes the advantages of Michael Burawoy's project while overcoming its principal limitations.